PENGARUH MOTIVASI KERJA, DISIPLIN KERJA DAN KOMPENSASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI RUMAH MAKAN SATE KLATAK PAK PONG (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2022)
This research aims to analyze (1) the effect of work motivation on the work productivity of employees at Sate Klathak Pak Pong Restaurant, (2) the effect of work discipline on employee productivity of employees at Sate Klathak Pak Pong Restaurant, (3) the effect of compensation for productivity Employee work at the Sate Klathak Pong Pong Restaurant, the effect of motivation, work discipline, and compensation for the work productivity of employees at Sate Klathak Pak Pong Restaurant. This research uses the Causal Associative method using a quantitative approach. The population in the study was an employee at Sate Klathak Pak Pong Restaurant. Sampling techniques use random Sampling with a total sample of 100 people. Data collection techniques using a questionnaire that has been tested for validity and reliability. Data analysis techniques use multiple regression. The results showed that: (1) work motivation has a negative effect on the work productivity of employees at Sate Klathak Pak Pong Restaurant (t count = -2.144; significance value of 0.35less than 0.05; and regression coefficient = - 0.318); 2) Work discipline does not affect the work productivity of employees at Sate Klathak Pak Pong Restaurant (t count = 0.588; significance value of 0.558 greather than 0.05; and Regression coefficient = 0.94); Compensation has a positive effect on productivity employee work at Sate Klathak Pak Pong Restaurant (T count = 7,437; significance value of 0,000less than0.05; regression coefficient = 0.768).
Keywords: work motivation; work discipline; compensation; and work productivity